2016
DOI: 10.1111/all.12937
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 inhibition prevents lung inflammation, remodeling, and accumulation of Th2 and Th17 cells in a murine asthma model

Abstract: HDM-induced airway inflammation, remodeling, and Th2/Th17-type cell accumulation involve STAT3 activation that can be prevented by C188-9 treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 38 publications
9
66
0
Order By: Relevance
“…Th2 cytokines IL-4 and IL-13 can activate epithelial and endothelial cells and fibroblasts to produce eotaxin, a chemotaxin important for recruiting eosinophil from the airway microvessels into the lung tissue [35]. Recently, compelling evidences have demonstrated that Th17 cells are a major player to the pathogenesis of allergic airway inflammation, especially to severe asthma [22, 23, 29, 3840]. The latter is often induced by infection and resistant to steroid therapy in patients [41].…”
Section: Discussionmentioning
confidence: 99%
“…Th2 cytokines IL-4 and IL-13 can activate epithelial and endothelial cells and fibroblasts to produce eotaxin, a chemotaxin important for recruiting eosinophil from the airway microvessels into the lung tissue [35]. Recently, compelling evidences have demonstrated that Th17 cells are a major player to the pathogenesis of allergic airway inflammation, especially to severe asthma [22, 23, 29, 3840]. The latter is often induced by infection and resistant to steroid therapy in patients [41].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mouse models show that persistent IL-17 activation leads to increased collagen deposition, airway smooth muscle mass, and mucous hypertrophy in a mouse model of asthmatic airway remodeling [21]. More recently, we demonstrated that airway inflammation and remodeling in the murine house dust mite (HDM) model of asthma is accompanied by STAT3 activation within the lung and by increased lung levels of Th2- as well as Th17-type cytokines [22]. …”
Section: Stat3 and Asthmamentioning
confidence: 99%
“…We showed that systemic administration C188-9, abrogated HDM-induced STAT3 activation, airway inflammation, and remodeling. Inhibition of HDM-induced lung changes by C188-9 was accompanied by normalization of IL-4, IL-5, IL-13, and IL-17A cytokine levels, as well as prevention of HDM-induced increases in Th2 cells, Th17 cells, and IL-4- and IL-17A-producing non-T cells [22]. Available data suggest there may be a therapeutic advantage of targeting both Th2 and Th17 in asthma to maximize therapeutic efficacy [69], which C188-9 may be able to provide.…”
Section: Stat3 and Asthmamentioning
confidence: 99%
“…Th2 and Th17 inflammatory pathways seemed to be reciprocally regulated in asthma [41]. On the other hand, CpG-oligodeoxynucleotides [37], STAT3 inhibition [42], CB2 receptors on NK cells [31] or secretoglobin superfamily protein SCGB3A2 [33] suppressed allergen-induced asthma in mice. Thus, the investigated factors illustrate that asthma can be counterregulated by reinforcing tolerance or skewing Th2-based asthma towards Th1 or Th17.…”
Section: Introductionmentioning
confidence: 99%